Toward a Holistic Communication Approach to an Automated Vehicle's Communication With Pedestrians: Combining Vehicle Kinematics With External Human-Machine Interfaces for Differently Sized Automated Vehicles - Lau, Merle; Jipp, Meike; Oehl, Michael (Frontiers in Psychology, 2022)
Future automated vehicles (AVs) of different sizes will share the same space with other road users, e.g., pedestrians. For a safe interaction, successful communication needs to be ensured, in particular, with vulnerable road users such as pedestrians. Two possible communication means exist for AVs: The vehicle kinematics for implicit communication and external humanmachine interfaces (eHMIs) for explicit communication. However, the exact interplay is not sufficiently studied yet for pedestrians’ interactions with AVs. Additionally, very few other studies focused on the interplay of vehicle kinematics and eHMI for pedestrians’ interaction with differently sized AVs, although the precise coordination is decisive to support the communication with pedestrians. Therefore, this study focused on how the interplay of vehicle kinematics and eHMI affects pedestrians’ willingness to cross, trust and perceived safety for the interaction with two differently sized AVs (smaller AV vs. larger AV). In this experimental online study (N = 149), the participants interacted with the AVs on a shared space. Both AVs were equipped with a 360° LED light-band eHMI attached on the outer vehicle body. Three eHMI status (no eHMI, static eHMI, dynamic eHMI) were displayed. The vehicle kinematics were varied at two levels (non-yielding vs. yielding). Moreover, “nonmatching” conditions were included for both AVs in which the dynamic eHMI falsely communicated a yielding intent although the vehicle did not yield. Overall, results showed that pedestrians’ willingness to cross was significantly higher for the smaller AV compared to the larger AV. Regarding the interplay of vehicle kinematics and eHMI, results indicated that a dynamic eHMI increased pedestrians’ perceived safety when the vehicle yielded. When the vehicle did not yield, pedestrians’ perceived safety still increased for the dynamic eHMI compared to the static eHMI and no eHMI. Findings of this study demonstrated possible negative effects of eHMIs when they did not match the vehicle kinematics. Further implications towards a holistic communication strategy for differently sized AVs will be discussed.